SPECIFIC ASPECTS OF DIGITAL TECHNOLOGIES IN PHYSICS TEACHING (Universal International Scientific Journal, 2026)
This article examines the relevance of introducing the achievements of digital technologies in physics teaching today, and what aspects should be considered when creating national content for virtual laboratories in this area.
Keywords: physics, digital technologies, virtual laboratory, platform, electronic resources, computer, content, digital resources, interactivity.